Understanding Consumer Attitudes and Behavioral Intentions Toward Electric Vehicles: Evidence from Sustainable Consumption in Indonesia - Robetmi Jumpakita Pinem; Ari Pradhanawati; Pan Guangmei (AIBPM Publisher, 2026)
The adoption of electric vehicles (EVs) in Indonesia remains relatively low despite strong market potential and increasing environmental concerns. This study aims to examine the influence of esteem needs, cost savings, infrastructure, and ease of operation on consumer attitudes toward EVs and their subsequent behavioral intentions. A quantitative approach was employed using a survey of 100 EV users in Central Java and Jakarta, with data analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that ease of operation (? = 0.332, p 0.05) is the strongest predictor of attitude, followed by esteem needs (? = 0.280, p 0.05) and cost savings (? = 0.248, p 0.05), while infrastructure has no significant effect (? = 0.070, p 0.05). Attitude significantly influences behavioral intention (? = 0.760, p 0.001) and mediates the effects of the significant predictors. These findings indicate that EV adoption in Indonesia is driven more by psychological and economic factors than by infrastructure readiness. The study extends the TAM by integrating these factors within a sustainable consumption context. Practically, policymakers and marketers should emphasize ease of use, cost benefits, and symbolic value to accelerate adoption.